2020
DOI: 10.3390/biology9040076
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification and Evaluation of the Genetic Diversity of Dendrobium Species Collected in Southern Vietnam

Abstract: Dendrobium has been widely used not only as ornamental plants but also as food and medicines. The identification and evaluation of the genetic diversity of Dendrobium species support the conservation of genetic resources of endemic Dendrobium species. Uniquely identifying Dendrobium species used as medicines helps avoid misuse of medicinal herbs. However, it is challenging to identify Dendrobium species morphologically during their immature stage. Based on the DNA barcoding method, it is now possible to effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…Previous studies showed that diterpenoids extracted from C. kongensis had many biological activities in vitro, including antioxidant, anti-inflammatory, antibacterial, and anticancer [1][2][3][4]. Particularly, the anticancer activity of these diterpenoids had been presented on liver cancer cells and colorectal cancer cells by inducing apoptosis via activating related signaling pathways [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that diterpenoids extracted from C. kongensis had many biological activities in vitro, including antioxidant, anti-inflammatory, antibacterial, and anticancer [1][2][3][4]. Particularly, the anticancer activity of these diterpenoids had been presented on liver cancer cells and colorectal cancer cells by inducing apoptosis via activating related signaling pathways [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Many endemic plants of Vietnam have been used as traditional medicines for thousands of years [1][2][3][4].…”
Section: Introduction *mentioning
confidence: 99%
“…Dendrobium, also known as "Shihu", belongs to the orchid family. 1,2 Although seventy-four species and two varieties are known, only about forty species have medicinal value. Furthermore, some of these species with high medicinal values are now endangered.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular markers have been developed and a variety of molecular markers have been used to detect genetic diversity and genetic relationships among species in the genus Dendrobium to date, including random-ampli ed polymorphic DNA (RAPD) (Zhu et al 2011), inter simple sequence repeat (ISSR) ), simple sequence repeat (SSR) (Lu et al 2013; Kang et al 2015), sequence related ampli ed polymorphism (SRAP) (Feng et al 2014), inter primer binding repeats site (iPBs) (Cui et al 2020), target region ampli cation polymorphism (trap) (Feng et al 2015), sequence-characterized ampli ed regions (scar) (Zheng et al 2021), these markers are based on electrophoretic map. Other markers are based on sequence differences, including nuclear genome such as ITS, chloroplast genome, including matK, rbcL, psbA-trnH and mitochondrial genome (Ye et al 2017;Wang et al 2018;Nguyen et al 2020). These studies showed that highly genetic differentiation and rich genetic diversity existed among different Dendrobium species.…”
Section: Introductionmentioning
confidence: 99%